1987
DOI: 10.1159/000261011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xylitol and Sorbitol on Polysaccharide Production by and Adhesive Properties of Streptococcus mutans

Abstract: Batch culture techniques were used to study the effect of sorbitol and xylitol on the aggregation, adhesion and solubility of the polysaccharides produced by Streptococcus mutans in the presence of 3% sucrose. Both polyols increased the production of soluble polysaccharides: control < xylitol < sorbitol. The presence of sorbitol increased also the amount of insoluble carbohydrates associated with the cell mass, whereas xylitol decreased the amount of these polysaccharides compared to the control. The highest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
8

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 13 publications
2
31
0
8
Order By: Relevance
“…This finding may be in agreement with previous observations on the general increase in plaque nitrogen (and protein) metabolism in a situation where plaque bacteria are affected by a nonglucose substrate such as xylitol [Mäkinen and Scheinin, 1975;Knuuttila and Mäkinen, 1981]. During a xylitol regimen, dental plaque actually loses portions of its polysaccharide content [Mäkinen et al, 1985;Söderling et al, 1987]. The present study used a 0.9% NaCl extract to study plaque protein levels, while Scheie et al [1998] used a deoxycholate solution.…”
Section: Discussionsupporting
confidence: 91%
“…This finding may be in agreement with previous observations on the general increase in plaque nitrogen (and protein) metabolism in a situation where plaque bacteria are affected by a nonglucose substrate such as xylitol [Mäkinen and Scheinin, 1975;Knuuttila and Mäkinen, 1981]. During a xylitol regimen, dental plaque actually loses portions of its polysaccharide content [Mäkinen et al, 1985;Söderling et al, 1987]. The present study used a 0.9% NaCl extract to study plaque protein levels, while Scheie et al [1998] used a deoxycholate solution.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also suggest the plausible mechanism linking xylitol gum chewing and oral bacteria quantity. The xylitol contained in xylitol chewing gum has been known to inhibit the growth, metabolism, and polysaccharide production of Streptococcus mutans (Söderling et al 1987(Söderling et al , 2008Söderling 2009). The subsequent decreased ability of biofilm formation may lead to a decrease in the amount of some kind of bacteria involved in the biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Other evidence has shown that xylitol leads to a reduction in the quantity of plaque, possibly by interfering with mechanisms of adhesion between plaque organisms and the tooth's surface. [65][66][67][68] This is the most likely explanation for the reduced colonisation of mutans streptococci in the mouths of these children.…”
Section: Specific Caries-preventive Actions Of Xylitolmentioning
confidence: 95%